Kierunki przekształceń wybranych elementów struktury Wrocławia w latach 90. XX wieku - Korenik, Stanisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
This paper discusses demographical tendencies in Wroclaw in 1990s. Other analyzed factors a population and qualitative features like kind of education and economic activity and differences of them among quarters of city. In the last 15 years changes in Wroclaw structure has been very intensive. They have been caused through endogenous as well as exogenous factors. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 49-58